Preliminary Study on Factors that Enhanced the Production of Uricase by Aspergillus Flavus - Siti Hatijah, Mortan; Wan Ruhayu, Wan Ramli (International Academy Publishing (IAP), 2013)
Urate oxidase or uricase is an enzyme that catalyses the oxidation of uric acid to allantoin and plays important rule in purine metabolism. The first important application discovered for uricase was in clinical biochemistry as diagnosis reagent for measurement of uric acid in blood. The precipitation of uric acid can leading to gout symptom. The main purpose of this research is to optimize the culture condition for maximum uricase production by Aspergillus flavus. The parameters studied were pH (ranged pH4 to pH8),the sucrose concentration (10g/l to 50 g/l) and the agitation rate(100 to 300 rpm). The Aspergillus flavus were inoculated in yeast extract with sucrose and incubated for 24 hours at 200 rpm and 30oC. The maximum enzyme activity obtained from the experiment is 0.03974 U/ml at pH 6, 200 rpm and 30 g/l sucrose concentration.